Monozygotic Triplets and Dizygotic Twins following Transfer of Three Poor-Quality Cleavage Stage Embryos - Reshef Tal; Dmitry Fridman; Richard V. Grazi (Hindawi Limited, 2012)
Background. Assisted reproductive technology has been linked to the increased incidence of monozygotic twinning. It is of clinical importance due to the increased risk of complications in multiple pregnancies in general and in monozygotic twins in particular. Case. A 29-year-old female, nulligravida underwent her first IVF cycle. Three poor-quality cleavage stage embryos were transferred resulting in monochorionic triamniotic triplets and dichorionic diamniotic twins. Selective embryo reduction was performed at 12 weeks leaving dichorionic twins. The patient underwent emergency cesarean section due to preterm labor and nonreassuring fetal heart tracing at 30 weeks of gestation. Conclusion. Our case emphasizes that even embryos with significant morphological abnormalities should be considered viable and the possibility of simultaneous spontaneous embryo splitting must be factored into determining number of embryos to transfer.